Ciudadanas para una nueva Argentina. Debates por la inclusión política de la mujer durante el peronismo - Ruffini, Martha (2016)
In 1947 the Argentine National Congress passed the law which gave women the right to vote, thus settling a long period of exclusion from the political citizenship. The legislative debates about the new national suffrage law show a decisive moment in the construction of the Peronist hegemony, evidenced by the need to unite the new force and generate the first symbolic constructions in which power was developing, constructions intended to give Peronism a history rooted to the past of the nation and give women a lasting connection with Eva Perón s figure and an essential role in the construction of the new Peronist Argentina.